(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
This study evaluates the seismic performance of exterior beam–column joints (BCJs) made with geopolymer concrete (GPC) as a sustainable alternative to Ordinary Portland Cement (OPC). GPC mixes incorporated Metakaolin (MK) and Ground Granulated Blast Furnace Slag (GGBS) as partial OPC replacements, targeting 30 MPa compressive strength. Three mixes were examined: M1 (control), M2 (60% OPC + 20% GGBS + 20% MK), and M3 (40% OPC + 30% GGBS + 30% MK). Three specimens were tested under monotonic lateral loading to assess cracking, strength, ductility, and energy absorption. Results showed that replacing OPC with GGBS and MK enhanced the seismic performance of BCJs. The control specimen (M1) exhibited brittle shear failure with wide cracks, limited energy dissipation (1461 kN-mm), and moderate ductility (μ = 4.71). In contrast, M2 demonstrated narrower cracks, improved stiffness, higher energy dissipation (1737 kN-mm), and the highest ductility (μ = 5.08), making it the most balanced mix. M3 showed the maximum load capacity (63.2 kN) and highest energy absorption (1851 kN-mm), but with reduced ductility (μ = 4.20), reflecting the brittleness of higher-strength mixes. The enhancements were ascribed to the generation of extra gel phases (C-(A)-S-H and N-A-S-H), which improved the microstructure, bond strength enhancement between the ground structure and the mortar, and stress transfer. Load-displacement curves exhibited a consistent elastic phase followed by progressive ductile failure for the modified mixes. The replacement of 20% of the OPC (M2), overall, showed the best combination of strength and ductility and was the most promising for seismic application. These findings highlight GPC as a high-performance, eco-efficient material that enhances the resilience of BCJs in earthquake-resistant structures while reducing OPC consumption and supporting sustainability.